The Effectiveness of Role-Play and Information-Gap in E – Teaching Speaking Skill for High-Low Self-Confident Students - Rafsanjani, Ali Akbar; Suwandi, Suwandi; Linggar Bharati, Dwi Anggani (English Education Journal, 2020)
Teaching speaking is not easy. The teacher has to use an appropriate technique in teaching speaking. The research problem came from the Eighth Grade students of SMPN 1 Arjawinangun Cirebon. The students were passive in conversation when someone talked in English because the teacher taught using traditional method which made them bored and could not give feedback in English conversation. On the students’ side, they get difficulties in learning speaking because they felt bored and passive during teaching and learning process. This research aims to explain how significant the students’ achievement taught by using role play and information gap technique conducted with high and low self-confident of students in e-teaching speaking context. The research design was a quasi-experimental design with a 2x2 factorial design involving the eighth-grade students SMPN 1 Arjawinangun, Cirebon as the research participants. There were two experimental groups involved. The students’ different self-confidence was taken as a factor that might influence the techniques. In collecting the data, the writer used speaking test to get students’ scores and questionnaires made by Google Form and on-line system. The data was analyzed using ANOVA to answer the main hypotheses. Based on the analysis of the significance score was 0.178 which was higher than 0.05. It can be concluded that there was no significant difference on the students’ achievement taught by role play and information-gap for students with high and low self-confidence. This research is expected to give a contribution to the research such as giving appropriate technique to teach speaking in e-learning.